THE ROLE OF TECHNOLOGY AND INNOVATION IN DEFENSE EQUIPMENT DEVELOPMENT IN INDONESIA: A QUALITATIVE STUDY ON THE NATIONAL DEFENSE INDUSTRY - Ega Adhisty Riani; I.B Putra Jandhana; Aries Sudiarso; Hariantana Aygy Yolanda (CV. AFDIFAL MAJU BERKAH, 2025)
This research aims to analyze the role of technology and innovation in the development of the main weaponry system (Alutsista) in Indonesia, with a focus on the domestic textile industry. This research uses a qualitative approach to analyze the dynamics of technological progress and innovation in Indonesia's textile industry. The data collection method includes 15 key informants, such as the Ministry of Defense, Defense Implementing Industries, and experts in the field of defense equipment technology. To supplement the primary data, industry and labor department reports were also analyzed. Data analysis used topic analysis techniques to identify primary and secondary themes. The fundamental conclusion of this study is that innovation and technology play an important role in improving the capability and productivity of the national manufacturing sector. However, there are some significant problems, such as aging technology, declining research and development funds, and so on.